Cultural Patterns in the Poetry of Baland Al-Haidari (Journal of the College of Basic Education, 2026)
By the late twentieth century, cultural criticism underwent a qualitative shift in its epistemological system, moving from a focus on the aesthetic singularity of literary texts to an exploration of discourses as manifestations of a broader cultural pattern that reflects the dynamics of social, historical, and political structures. Texts were no longer read as isolated aesthetic entities but became subjects of deconstruction and analysis aimed at uncovering the hidden mechanisms that shape collective consciousness and reproduce cultural identity. The concept of "pattern" expanded to encompass a network of values and norms, governed by a clear internal structure, defined boundaries, and social recognition of its function and Influence in shaping human experience. In this context, the poet Baland al-Haidari emerges as a unique model in employing cultural patterns in crafting his poetic text. Through a sharp critical vision, al-Haidari re-read religious and traditional symbols and concepts, not as static icons, but as living energies capable of interrogating contemporary reality and unveiling its hidden transformations. His return to heritage, therefore, was not a nostalgic retrieval of the past, but a creative act that reactivated memory within a critical horizon that transcended static reverence to interrogate the present and challenge its assumptions.Al-Haidari did not merely Invoke the religious pattern; his work also involved the deconstruction of historical and artistic frameworks. He employed heritage as a means to stimulate collective memory without fallIng into the trap of nostalgia. Instead, he dismantled the hegemonic grand narratives, liberated heritage from the grip of ideology, and opened it up to new possibilities of meaning. Myth, too, was present in his experience—not as linguistic ornament or rhetorical device, but as a reflective mirror of the contemporary existential crisis, where alienation, disorientation, and human anxiety prevail.Thus, Baland al-Haidari's text Illuminated itself through the interplay of patterns—where myth meets history, the sacred intertwines with the everyday, and memory merges with the present—creating a multilayered poetic fabrIc oscillating between a yearning for meaning and skepticism about grasping It, between invoking heritage and questioning it, between presence and absence in an excessively transformative world. Through this creative employment, al-Haidari succeeded in crafting a text that transcends the binary of tradition and modernity, expressing human anxiety and ontological questions in a fragmented age, thereby establishing a poetic experience marked by philosophical depth and a renewed cultural vision.